To solve the expression \( 10^{(2^3)} \cdot 10^{(3^3)} \), we first need to calculate the exponents:
-
Calculate \( 2^3 \): \[ 2^3 = 2 \times 2 \times 2 = 8 \]
-
Calculate \( 3^3 \): \[ 3^3 = 3 \times 3 \times 3 = 27 \]
Now, we can rewrite the expression using these values: \[ 10^{(2^3)} \cdot 10^{(3^3)} = 10^8 \cdot 10^{27} \]
Next, we can apply the property of exponents that states \( a^m \cdot a^n = a^{m+n} \): \[ 10^8 \cdot 10^{27} = 10^{(8 + 27)} = 10^{35} \]
Finally, the numerical equivalent of \( 10^{35} \) is: \[ 10^{35} = 100000000000000000000000000000000000000 \]
Thus, the final answer is: \[ \boxed{10^{35}} \] or in numerical form: \[ \boxed{100000000000000000000000000000000000000} \]